Shield current induced noise in audio cables - Chupakhin, A. (НТУ "ХПИ", 2013)
Take an experimental research the "shield-current-induced noise" measurement results for various types of audio cables and developed the circuit model to simulate a behavior of the various length cables in the 10 kHz – 4 MHz range.
Keywords: electromagnetic compatibility; radio frequency interference; shield-current-induced noise